Giant suppression of dielectric loss in BaZrO3 - Kolodiazhnyi, T.; Pulphol, P.; Vittayakorn, W.; Vittayakorn, N. (My University, 2019)
We report the effect of precursor's purity and heterovalent substitution on the microstructure and dielectric properties of BaZrO3 ceramics. We find that independent of the purity or raw materials, the dielectric loss of BaZrO3 at microwave frequencies is rather high with a Q factor in the range of 1000–3000 at 10 GHz. All stoichiometric ceramics studied show up to three types of low-T dielectric relaxations in the 2–250 K range. All these dielectric anomalies can be suppressed by partial substitution of Zr for Nb. By alloying of BaZrO3 with a hypothetical BaGa1/2Nb1/2O3 phase the Q × f value of ceramics at microwave frequency can be improved significantly. The origin of this remarkable improvement is attributed to the effect of the donor ions on the random electric fields and antiferrodistortive instability. Ceramic with a chemical composition of BaZr0.96Ga0.02Nb0.02O3 sintered at 1600 °C shows dielectric constant, ε′ = 36.7, temperature coefficient of the resonance frequency, τf = +110 ppm/°C and Q × f = 172 THz.
Keywords: BaZrO3; Dielectric loss; Dielectric resonators; Point defects; Sintering